Dual Anthropology as the Imago Dei in Edith Stein - Ales Bello, Angela (Open theology, 2019)
This essay consists of two parts. The first part deals with the birth of a dual anthropology in Edith Stein’s thought, whereas the second part treats the teleological origin of this duality. In order to explain how she elaborated her dual anthropology two themes become intertwined in my investigation: the question of the feminine in western culture and the teleological question of the human being as an image of God. In my discussion of the first theme, I examine both the historical development of the feminist movement, maintaining that the birth of the feminist movement in the West has its roots in Christianity, as well as the theoretical reflection of Edith Stein on a dual anthropology, which becomes ultimately linked to a theological framework and, hence, to the idea of "image." Here, we have to ask: What is the meaning of "image"? In what sense is the human being an image of God? Following the foregoing claim, I argue that Stein’s dual anthropology is very helpful in our time to clarify some questions that arise in connection with "gender theory".